Analisis Interaksi dan Perbedaan Pembelajaran Bersama dan Pembelajaran-Mandiri serta Motivasi terhadap Pengetahuan-diri pada Semester VII Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Mohammad Rodli (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
The purpose of this study are: 1) Describe the differences of self-knowledge with Learning together with self-learning in the seventh semester of Tarbiyah High School of Raden Wijaya Mojokerto. 2) Describe the difference of self-knowledge of high motivated and low motivated students in the seventh semester of Tarbiyah High School of Raden Wijaya Mojokerto 3) Describe the interaction between learning together with self-learning and self-knowledge motivation in semester VII Tarbiyah High School Tarriyah Raden Wijaya Mojokerto . The type of this research is survey type research with quantitative approach. Population as object of research is student of semester VII of Tarbiyah High School of Raden Wijaya Mojokerto, This research is included in research of comparative explanation. Data collection techniques used questionnaires, while data analysis techniques used multiple linear regression analysis, with hypothesis test using t test and F test. From the analysis result can be concluded as follows: 1) There is difference of self-knowledge with Learning together with self-learning. 2) There is no difference in self-knowledge that is highly motivated and students with low motivation. 3) There is an interaction between Learning along with self-learning as well as motivation to self-knowledge.